The Relationship between Physical Punishment at Home and Victimization from Peer Aggression at School in Adolescents in Iran and Finland: A Mediator?Moderator Analysis (European Journal of Social Science Education and Research, 2020)
The aim of the study was to investigate whether depressive symptoms could serve as a mediator between the experience of physical punishment in childhood and victimization from peer aggression at school, as has been shown by Söderberg et al. (2016). An aggregated sample consisting of 1,001 Iranian adolescents and 2,205 Finnish adolescents, all 13-15 years of age, participated in the study. Data were analyzed with conditional process modeling (Preacher - Hayes, 2008). The hypothesis was only partially corroborated. Depression served only as a weak mediator, and not at all among Iranian boys. The results are discussed.